2023
DOI: 10.1158/0008-5472.can-22-2053
|View full text |Cite
|
Sign up to set email alerts
|

Are There Specific Cancer Stem Cell Markers?

Abstract: The cancer stem cell (CSC) model states that heterogeneous tumor cell populations are organized in a hierarchical manner, with a small population of CSCs at the apex. These CSCs are capable of self-renewal and giving rise to other cancer cell populations, conceptually analogous to the function of normal adult stem cells present in almost all organs. However, there has been significant controversy regarding the existence and identification of CSCs. We argue that technical differences in experimentation and CSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Cancer tissue consists of heterogeneous cell types, and each subpopulation has plasticity to turn into the others. Cancer stem cells (CSCs) are a subpopulation that possesses therapeutic resistance and tumor reconstruction capability and are responsible for cancer progression [ 18 20 ]. Considering that ELF4 was reported to affect cancer stemness in many cancers [ 21 , 22 ], we performed relevant in vitro and in vivo assays.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer tissue consists of heterogeneous cell types, and each subpopulation has plasticity to turn into the others. Cancer stem cells (CSCs) are a subpopulation that possesses therapeutic resistance and tumor reconstruction capability and are responsible for cancer progression [ 18 20 ]. Considering that ELF4 was reported to affect cancer stemness in many cancers [ 21 , 22 ], we performed relevant in vitro and in vivo assays.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been controversy regarding the identification of CSCs primarily due to the technical differences in experimentation and CSC assays, etc. 42 . How tumor-initiating cells are defined or supported in this study is by various means, including correlation with CD133 which is a widely reported surrogate marker of liver cancer stem cells 5 , 6 , 8 , (ii) correlation with stemness/undifferentiated signatures defined by CytoTRACE 27 and cancer stemness index 30 , etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro clonal assay studies have demonstrated the expression of PROP1, PRX1/2, GFRα2, CXCR4, and NESTIN in PSC ( Horiguchi et al, 2012 ; Rizzoti et al, 2013 ; Higuchi et al, 2014 ). Notably, cancer cells with stem cell properties are called cancer stem cells (CSC), and these cells can self-regenerate and differentiate into all cell types within the tumor ( Batlle and Clevers, 2017 ; Steinbichler et al, 2018 ; Lan and Behrens, 2023 ). More recent studies have identified these cells in pituitary adenomas ( Carreno et al, 2017 ; Cox et al, 2017 ; Lodge et al, 2019 ).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…PPA is characterized by its aggressiveness and high postoperative recurrence rate ( Steinbichler et al, 2018 ; Lodge et al, 2019 ; Lan and Behrens, 2023 ). Transsphenoidal microsurgical resection of mixed pituitary adenomas remains the preferred treatment for PPA ( Swearingen, 2012 ; Ammirati et al, 2013 ).…”
Section: Potential Mechanismsmentioning
confidence: 99%